Removal of nutrients and organic pollutants from household greywater by phycoremediation for safe disposal - Mohamed, R. M.; Al-Gheethi, A. A.; Aznin, S. S.; Hasila, A. H.; Wurochekke, A. A.; Kassim, A. H. (Springer International Publishing, 2017)
The present study aimed to investigate the potential for application of phycoremediation system using Botryococcus sp. for the treatment of bathroom greywater at village houses. The greywater samples were obtained from four houses. The treatment system was conducted at ambient temperature for 21 days. Botryococcus sp. (Ac-cession No. JQ585723.1) was inoculated into the greywater in a dry mass (0.3 mg L-1). The results revealed high effectiveness of the treatment system. The maximum reduction of biological oxygen demand (BOD5) from four types of greywater ranged from 85.3 to 98%, while was between 71.22 and 85.47% for chemical oxygen demand (COD) after 21 days. The reduction of nitrate (NO3-) appeared rapidly within 18 days of the treatment period with 98% of the reduction efﬁciency. Reduction of ammonia (NH3) and orthophosphate (PO43-) was recorded after 21 days with the efﬁciency ranged from 86.21 to 99 and 39.12 to 99.3%, respectively. The high removal per-centage of potassium (K) (97%) recorded within 3 days, while calcium (Ca) reduction (95%) was noted at the end of the treatment period indicating the high applicability of phycoremediation system to be used in the village houses. Moreover, the system is easily implementable, very low cost where no energy is required, eco-friendly and has no toxic by-products.